The absence of a system of internal controls in South African Administrative Law, in light of Section 7(2) of the Promotion of Administrative Justice Act 3 of 2000 - Heydenrych, Ernst (Stellenbosch : Stellenbosch University, 2020)
Thesis (LLM)--Stellenbosch University, 2020.